(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Visitor satisfaction is a key factor for every tourist destination to be able to continue to run its operations. Visitors who feel satisfied will have various good impacts on the sustainability of tourist attractions in a sustainable manner. This study tested the role of service quality, promotion and destination image on visitor satisfaction at the Subak Teba Majalugu Educational Tour in Denpasar. The population of this study was all visitors to the Subak TeBA Majalgu Education Tour during 2022, namely 2,942 people with a total sample obtained using the slovin formula of 80 people. Testing for the proposed hypothesis was carried out by means of multiple linear regression analysis. The results were found after testing, namely both partial tests and simultaneous tests of service quality, promotion and destination image showing a positive and also significant influence on visitor satisfaction. It is suggested to managers to improve service quality, promotion and destination image so that visitor satisfaction increases.